Johannes Ewald i romanhistorien. En omdatering og revurdering af Herr Panthakaks Historie - Gjerlevsen, Simona Zetterberg (Passage - Tidsskrift for litteratur og kritik, 2016)
Simona Zetterberg Gjerlevsen: “Johannes Ewald in the History of the Novel. A Redating and Revaluation of The Story of Mr. Panthakak” The article undertakes an investigation of the relationship between two of Johannes Ewald’s prose works: The Story of Mr. Panthakak and an abstract from the journal The Foreigner. In so doing, the article disproves prevailing assumptions of the dating of The Story of Mr. Panthakak as it provides evidence that the story is written later than The Foreigner. This has important consequences for the view of Ewald’s authorship since The Story of Mr. Panthakak makes use of a number of fictionality techniques such as zero focalization, meta commentaries, fictive characters and unrealistic events associated with the novel. Accordingly, this article suggests that a redating of The Story of Mr. Panthakak together with an attention to its techniques of fictionality show that Ewald anticipated what was to become the dominating literary genre: the novel.